PROSPECTS OF CONCEPTUALIZATION OF THE NOTION “HEREDITY” - A. A. Kochergin (Научный вестник МГТУ ГА, 2016)
The article examines the prospects for further development of the conceptualization of the notion “heredity” in a wide range of biological and socio-humanitarian aspects. Further development of genetics closely relates to the disclosure of interaction of genetic, interdisciplinary, general scientific, ethical, legal and philosophical categories, its complex dialectics. The doctrine of heredity in the post-nonclassical stage of its development is increasingly taking on the traits of humanities, of a science of human.